Anemia y factores asociados en gestantes atendidas en el Centro de Salud Universitario de Motupe-Loja - Ayala Espinoza, Nerida Mireya (2023)
Anemia during pregnancy is a worldwide public health problem, a very frequent alteration that is associated with multiple factors such as the inter-gestational period, number of prenatal checkups, patient´s age and education, as well as socioeconomic level. The objectives were to determine anemia and associated factors, specifically to determine the prevalence of gestational anemia, to identify the main sociodemographic and clinical factors associated with it, and to establish the relationship between these two variables in pregnant women attended at the University Health Center of Motupe. A descriptive cross-sectional-retrospective study was carried during the 2021-2022 year with a universe of 208 pregnant women, 41of whom met the inclusion criteria. The data were collected from patients' medical records. After analyzing the information, it was obtained that the prevalence according to clinical severity, mild anemia was more frequent with 75.6%, having that the main factors identified are patients with adolescent pregnancy, low level of education, of rural origin, with an inter-gestational period of more than 5 years, with unfavorable nutritional status and with inadequate prenatal controls during their pregnancy. No statistically significant association was found between sociodemographic and clinical factors with the main study variable anemia, either because there are characteristics of each population, so the results are different from what other authors mention